Hepatic Oxi-Inflammation and Neophobia as Potential Liver–Brain Axis Targets for Alzheimer’s Disease and Aging, with Strong Sensitivity to Sex, Isolation, and Obesity - Juan Fraile-Ramos; Anna Garrit; Josep Reig-Vilallonga; Lydia Giménez-Llort (Cells, 2023)
Research on Alzheimer’s disease (AD) has classically focused on alterations that occur in the brain and their intra- and extracellular neuropathological hallmarks. However, the oxi-inflammation hypothesis of aging may also play a role in neuroimmunoendocrine dysregulation and the disease’s pathophysiology, where the liver emerges as a target organ due to its implication in regulating metabolism and supporting the immune system. In the present work, we demonstrate organ (hepatomegaly), tissue (histopathological amyloidosis), and cellular oxidative stress (decreased glutathione peroxidase and increased glutathione reductase enzymatic activities) and inflammation (increased IL-6 and TNF𝛼) as hallmarks of hepatic dysfunction in 16-month-old male and female 3xTg-AD mice at advanced stages of the disease, and as compared to age- and sex-matched non-transgenic (NTg) counterparts. Moreover, liver–brain axis alterations were found through behavioral (increased neophobia) and HPA axis correlations that were enhanced under forced isolation. In all cases, sex (male) and isolation (naturalistic and forced) were determinants of worse hepatomegaly, oxidative stress, and inflammation progression. In addition, obesity in old male NTg mice was translated into a worse steatosis grade. Further research is underway determine whether these alterations could correlate with a worse disease prognosis and to establish potential integrative system targets for AD research.